Anticipated and unanticipated oil price shocks and optimal monetary policy - Hans-Werner Wohltmann; Roland C. Winkler (Kiel University, Department of Economics, 2008)
This paper studies the welfare effects of severalmonetary policy rules in the presence of anticipated and unanticipated oil price shocks. Our analysis is based on a stylized New Keynesian model of a small open economy. Our main findings are the following: i) Standard interest rate rules amplify the welfare loss compared to neutral monetary policies. ii) The optimal policy under commitment, by contrast, dampens the welfare loss. iii) Optimized simple rules can replicate the outcome under the optimal unrestricted rule if they are history-dependent, contain the exchange rate and, in the anticipated case, forward-looking elements. iv) Anticipated oil shocks lead to a higher welfare loss than unanticipated shocks.
Keywords: E32; E52; F41; 330; Anticipated Shocks; Oil Price Shocks; Open Economy; Optimal Monetary Policy; Simple Policy Rules; Geldpolitik; Mineralölpreisschock; Erwartungstheorie; Wohlfahrtseffekt; Ungleichgewichtstheorie; Kleines-offenes-Land; Theorie